Real Driving Emissions in Extended Driving Conditions - Danilo Engelmann (MDPI AG, 2021)
The real driving emission (RDE) testing for certification of vehicles is performed in conditions that are well defined in legislation. For emissions inventories and for research, the influences of some extended driving conditions on emissions are an interesting issue. In the present work, some examples of RDE results from two common passenger cars with gasoline and diesel propulsion are given. The varying driving conditions were “winter/summer”, “mild/aggressive”, and “higher altitude/slop”. The driving conditions: “winter”, “aggressive”, and “higher slope/altitude” generally require more energy, cause higher fuel consumption, and therefore, higher CO2-emissions. The condition of “winter driving”, especially in the urban type of operation, may cause some longer phases with not enough warmed-up exhaust aftertreatment and consequently some increased gaseous emissions. The DPF eliminates the nanoparticles (PN) independently on the driving conditions. Nevertheless, the DPF regeneration has an influence on the CO2-normality of the trip. The CO2-normality primary tolerance range can also be exceeded with aggressive driving. The elaborated results confirm the usefulness of the existing legal limits for the driving conditions of RDE homologation tests.